(untitled) (Вісник: Міжнародні відносини, 2025)
Background. The article is devoted to the analysis of China’s climate policy in the context of global climate change. The author examines the evolution of China’s approaches to solving environmental problems, starting from economic dominance over natural resources in the middle of the 20th century to the integration of the principles of sustainable development into modern state policy. Key internal and external factors that have influenced the formation of China’s climate strategy are examined, including threats from climate change, environmental crisis, public pressure, and participation in international agreements. Particular attention is paid to China’s commitment to achieving carbon neutrality by 2060 and adapting its energy policy to reduce greenhouse gas emissions. The article also analyzes the internal contradictions of China’s climate policy, the impact of an authoritarian governance system, and China’s pursuit of global leadership in the green economy. Methods. The study of China’s climate policy is interdisciplinary, so the work combines the tools of international political science, environmental studies, economics, and sociology. The following scientific methods and approaches were used: analysis of political documents and official sources, historical method, comparative analysis, systematic approach, critical analysis, and prognostic method. Results As part of the study, it was found that China’s climate policy is a complex and contradictory phenomenon formed under the influence of both global challenges and domestic socio-economic needs. While China is a leader in the development of renewable technologies and promotes sustainable development goals, these efforts are often motivated by a desire for energy security, economic modernization, and political influence on the international stage. The author notes that China’s active role in the fight against climate change can serve as a platform for strengthening its global authority. Still, internal contradictions and policy fragmentation create risks for sustainable development in this area. Conclusions. The analysis of China’s environmental policy in the era of global climate change allowed us to conclude that China’s climate policy is multidimensional and combines domestic needs with global obligations. China has identified climate change as a civilizational threat, which encourages the integration of environmental goals into the national development strategy. The main drivers of this policy are the need to solve internal environmental problems, such as air and water pollution, strengthen energy security, and modernize the economic model. The author emphasizes that China’s commitment to achieving carbon neutrality by 2060 and reducing emissions by 2030 are essential steps that meet international standards. At the same time, these initiatives serve as a tool for strengthening China’s international authority and consolidating its position as a global leader in the field of green economy. However, the author emphasizes the contradictions of climate policy, which arise due to management fragmentation, competition between local and central authorities, and the influence of economic interests of state and private structures. Despite progress in implementing low-carbon technologies, China’s policies remain dependent on domestic challenges, such as the need to support economic growth and social stability. In general, the author concludes that China’s climate policy has the potential to become a platform for international leadership, but its implementation will depend on the ability to resolve internal contradictions and adapt the political system to the needs of sustainable development.